The Teaching of EFL Writing in Indonesia - Ariyanti, Ariyanti (Dinamika Ilmu, 2016)
Writing is one of the most important aspects in English language acquisition. Teaching writing has its own challenges since there are some steps and requirements that teachers should prepare to undertake in the classroom. This article is aimed to discuss teaching and learning writing in the classroom based on theoretical conceptualisation. In addition, curriculum of teaching writing will be another important factor to consider as well as research and practice in teaching writing. Based on comparison to many theoretical concepts from various researchers, it shows that most of Indonesian students still struggle to figure out their problems of grammatical area. The biggest challenge is derived from the difference in cultural backgrounds between the students’ mother tongue and English, so it is possible to know the production of their writing does not ‘sound’ well in appropriate culture of English. Several problems also occur when the teachers have big classes to teach and the result of teaching writing to the students may be defeated. In this case, time also being a big challenge for the teachers to have the students’ writing improve because to accomplish a good composition in English, it needs complex steps such as brainstorming, prewriting, drafting, and editing. However, new techniques in teaching writing are needed to develop the students’ writing outcomes.